Stressful Life Events and Cognitive Decline: Sex Differences in the Baltimore Epidemiologic Catchment Area Follow-Up Study - Munro, Cynthia A. (Int J Geriatr Psychiatry, 2019)
INTRODUCTION: The reasons why women are at higher risk than men for developing dementia are unclear. Although studies implicate sex differences in the effect of stress on cognitive functioning, whether stressful life events are associated with subsequent cognitive decline has received scant research attention. METHODS: In Wave 3 (1993–1996) of the Baltimore Epidemiologic Catchment Area study, 337 men and 572 women (mean age = 47 years) reported recent (within the last year) and remote (from 1981 until 1 year ago) traumatic events (e.g., combat) and stressful-life events (e.g., divorce/separation). At Wave 3 and Wave 4 (2004–2005), they completed the Mini Mental State Examination (MMSE) and a word-list memory test. Multivariable models were used to examine the association between traumatic and stressful-life events at Wave 3 and cognitive change by Wave 4. RESULTS: A greater number of recent stressful life events at Wave 3, but not of more remote stressful events, was associated with greater verbal memory decline by Wave 4 in women but not in men. Stressful events were not associated with change in MMSE, and there were no associations between traumatic events occurring at any time and subsequent memory or MMSE decline in either sex. CONCLUSIONS: Unlike men, middle-aged women with a greater number of recent stressful life events demonstrate memory decline over a decade later. Sex differences in cognitive vulnerability to stressful life events may underlie women’s increased risk of memory impairment in late life, suggesting that stress reduction interventions may help prevent cognitive decline in women.